2021
DOI: 10.1007/s40261-021-01061-2
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic Acid Compared with Enoxaparin for the Prevention of Thrombosis and Mechanical Ventilation in COVID-19 Patients: A Retrospective Cohort Study

Abstract: Background and Objective Low-dose acetylsalicylic acid (ASA, aspirin) is a well-known and frequently studied drug for primary and secondary prevention of disease due to its anti-inflammatory and coagulopathic effects. COVID-19 complications are attributed to the role of thrombo-inflammation. Studies regarding the use of low-dose ASA in COVID-19 are limited. For this reason, we propose that the use of low-dose ASA may have protective effects in COVID-19-related thromboembolism and lung injury. This study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
10
0
6
Order By: Relevance
“…Recent data suggest that aspirin use is associated with improved COVID-19 patient outcomes, including decreased risk of thromboembolism, mechanical ventilation, ICU admission, and mortality [ [90] , [91] , [92] , [93] , [94] , [95] , [96] ]. Aspirin has been proposed to act on the intracellular signaling pathway involved with viral replication and reduction in systemic inflammation, cytokine release, platelet activity, and hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data suggest that aspirin use is associated with improved COVID-19 patient outcomes, including decreased risk of thromboembolism, mechanical ventilation, ICU admission, and mortality [ [90] , [91] , [92] , [93] , [94] , [95] , [96] ]. Aspirin has been proposed to act on the intracellular signaling pathway involved with viral replication and reduction in systemic inflammation, cytokine release, platelet activity, and hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients received aspirin 81 mg daily. A single retrospective cohort study evaluated confirmed COVID-19 patients divided into four treatment groups: control (who did not receive aspirin, enoxaparin, or other antiplatelet or anticoagulation agents), aspirin alone, enoxaparin alone, or concomitant use of aspirin and enoxaparin [ 91 ]. Aspirin use included dosing of 81–162 mg daily within 7 days prior to or within 24 h following COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective trial conducted in Egypt by Abdelwahab et al found that the risk of stroke or MI among patients on chronic aspirin therapy was significantly lower than among non-users after adjustment ( p = 0.02), but anticoagulants were found to be even more effective (adjusted OR = 0.071, p < 0.001) ( Abdelwahabet al, 2021 ). The essence of coagulopathy in COVID-19 is indeed hypothesized to be massive fibrin formation.…”
Section: Aspirin and Covid-19mentioning
confidence: 99%
“…Antiplatelets were not found to affect the need for or time to mechanical ventilation, nor the risk of acute respiratory distress syndrome (ARDS) upon admission among patients on aspirin or other anti-platelets (taken as primary or secondary cardiovascular prophylaxis or as treatment for thromboembolic disease) ( Pan et al, 2019 ; Russo et al, 2020 ; Tremblay et al, 2020 ; Abdelwahab et al, 2021 ; Banik et al, 2021 ). Limitations within these studies include failure to adjust for smoking status and BMI, small sample size ( Abdelwahab et al, 2021 ), inclusion of only inpatients ( Abdelwahab et al, 2021 ), and lack of correction for the influence of post-admission treatments ( Tremblay et al, 2020 ). Banik et al were able to detect a positive effect of anti-coagulants on mechanical ventilation need but found no correlation between antiplatelets and intubation ( Banik et al, 2021 ).…”
Section: Aspirin and Covid-19mentioning
confidence: 99%